Preparation method and application of MnSm hydrotalcite derivative catalyst for low-temperature SCR (Selective Catalytic Reduction) degradation

The preparation of MnSm hydrotalcite-derived composite metal oxide catalysts by co-precipitation method solves the problems of poor catalytic activity of existing SCR catalysts under low temperature conditions and narrow operating temperature windows, and achieves efficient degradation of NOx in the mobile source exhaust gas, which is suitable for industrial production.

CN119793444APending Publication Date: 2025-04-11CHONGQING UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510079736.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing SCR catalysts have poor catalytic activity under low temperature conditions, narrow operating temperature window, and traditional V2O5/TiO2 catalysts have biotoxicity problems, making it difficult to effectively degrade NOx in the exhaust gas of mobile sources.

Method used

The MnSm hydrotalcite-derived composite metal oxide catalyst was prepared by co-precipitation method. By co-precipitation of Mn(NO3)2·4H2O and Sm(NO3)3·4H2O under alkaline conditions, a catalyst with high and low temperature catalytic activity and a wide operating temperature window was formed.

Benefits of technology

The NO conversion rate at 150℃ is achieved to reach 93%, the NO conversion rate at the optimal active temperature of 150-250℃ reaches 98.47%, and the operating temperature window T80 is 150-350℃. At the same time, the process is simple and the cost is low, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005248191780000011
    Figure HDA0005248191780000011
  • Figure HDA0005248191780000012
    Figure HDA0005248191780000012
Patent Text Reader

Abstract

The invention relates to a preparation method of a MnSm-LDHs catalyst which is prepared by adopting a coprecipitation method and is derived from MnSm-LDHs as a precursor through roasting activation and application of the MnSm-LDHs catalyst. According to the catalyst, Mn is used as an active metal, doped Sm is used as an auxiliary agent, catalytic active species are inserted between hydrotalcite layers, hydrotalcite is used as a precursor, and the high-dispersion composite metal oxide type catalyst can be prepared through activation. The preparation method comprises the following steps: firstly, weighing Mn (NO3) 2.4 H2O and Sm (NO3) 3.4 H2O according to a stoichiometric ratio, adding a proper amount of deionized water, dissolving the Mn (NO3) 2.4 H2O and the Sm (NO3) 3.4 H2O to obtain a metal salt solution, adding an alkaline stabilizer into the deionized water to prepare a stabilizer solution, weighing Na2CO3 with the same mole number as metal ions, dissolving the Na2CO3 into the deionized water to prepare a precipitant, and adding the precipitant into the deionized water to prepare a precursor solution; dropwise adding the metal salt solution into a precipitant sodium carbonate solution under constant-temperature stirring, and dropwise adding a precipitant in the process to control the pH to be stable; the preparation method comprises the following steps: dropwise adding the Mn1Sm < 0.75 >-LDO-Air-NaOH solution into a reaction kettle, stirring for 12 hours, then dropwise adding the Mn1Sm < 0.75 >-LDO-Air-NaOH solution into the reaction kettle, vigorously stirring and aging the turbid liquid for 12 hours under a constant-temperature condition after dropwise adding, adjusting parameters such as pH, aging time and precipitant types in the process, drying after filtering, roasting and activating in air, nitrogen and other atmospheres after drying, tabletting and grinding into a 20-40-mesh catalyst, namely the Mn1Sm < 0.75 The Mn1Sm < 0.75 >-LDO-Air-NaOH composite metal oxide type catalyst disclosed by the invention has relatively good C3H6-SCR activity in the whole temperature range, and can be used for effectively removing nitrogen oxides and hydrocarbons. Hydrotalcite is used as a precursor, a high-dispersion composite metal oxide catalyst can be prepared through activation, and the catalyst generally has the characteristics of uniform distribution of high-activity sites in transition metal content, small crystal grains, large specific surface area, good stability for inhibiting sintering and the like, so that the catalyst shows excellent catalytic performance; therefore, the catalyst has high C3H6-SCR catalytic activity in the whole temperature range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a MnSm hydrotalcite-derived catalyst for low-temperature C3H6-SCR degradation, in particular, a catalyst for effectively degrading the atmospheric pollutant NO, belonging to the field of waste gas treatment technology and environmental catalytic environment. Background Art

[0002] Nitrogen oxides (NO x ) is one of the main air pollutants, which not only harms human health, but also causes environmental pollution such as acid rain and photochemical smog. x The emission of NO is increasing year by year with the increase of mobile and fixed sources. Therefore, it is necessary to control NO x The emission of pollutants has become a mandatory law in our country and is one of the important contents of current air pollution control.

[0003] C3H6-SCR technology is currently the most promising technology for mobile source exhaust NO x One of the purification technologies, the core of which is the catalyst. Under the action of the catalyst, the external reducing agent or the reducing substance in the tail gas selectively converts NO x Reduced to N2, making NO in the exhaust gas x Therefore, C3H6-SCR degrades NO x The development of catalysts is imperative.

[0004] The traditional SCR catalyst V2O5 / TiO2 has a narrow operating window (300-400℃) and poor low-temperature catalytic activity, which limits its use as a catalyst for removing NO from mobile exhaust. x application, and V2O5 is biologically toxic. Layered double hydroxide (LDHs) catalysts show potential application prospects in fixed source denitrification reactions due to their good structural adjustability, high specific surface area and good redox performance. Therefore, some people tried to introduce LDHs to prepare Cu-based or Fe-based LDHs catalysts in mobile source denitrification (Wen N, Su Y, Deng W, et al. Synergy of CuNiFe-LDH based catalysts for enhancing low-temperature SCR-C3H6 performance: Surface properties and reaction mechanism [J]. Chemical Engineering Journal, 2022, 438: 135570.), which have excellent water and sulfur resistance, but low denitrification conversion rate. Therefore, in mobile source denitrification, it is urgent to modify LDHs catalysts to improve their low-temperature activity and broaden their operating temperature window.

[0005] The design idea of ​​this patent is to screen green, low-cost, non-toxic LDHs denitrification catalysts with better low-temperature denitrification activity and a widened temperature operating window. Literature reports that Mn-based catalysts have better low-temperature activity. We have done a lot of exploration work. We first explored the urea hydrothermal synthesis method, solvent-free method, citric acid complexation method, and co-precipitation method for LDHs precursor-derived catalysts with different Mn contents as active components, and found that the effects were not ideal; there are literature reports that doping metal additives can significantly improve the low-temperature activity of the catalyst, so we explored adding Co, Ni, Cu, Nb, Fe, La, and Zr additives to further improve the low-temperature activity of the catalyst. The effects of Co, Cu, Nb, Fe, La, and Zr additives were not satisfactory. It was thought that the metal composite oxide structure of Co, Cu, Nb, Fe, La, and Zr additives has the ability to store and release oxygen, and should have the ability to improve low-temperature activity, but it failed to show. Summary of the invention

[0006] The purpose of the present invention is to provide a preparation method and application of a MnSm hydrotalcite-derived catalyst for low-temperature C3H6-SCR degradation. The catalyst has good catalytic activity for the reaction of selectively reducing NO using a reducing agent C3H6, and denitrifies to generate harmless N2, H2O, and CO2. After a large number of exploratory experiments, we found that the co-precipitation method was used to prepare a composite metal oxide-type catalyst derived from a hydrotalcite precursor doped with Sm metal, with Mn as the active component. The catalyst has high catalytic low-temperature activity and a wide operating temperature window. The NO conversion rate is 93% at 150°C. When the optimal active temperature is 150-250°C, the NO conversion rate reaches 98.47%, and the operating temperature window T 80 The temperature of the catalyst is 150-350°C. In addition, the preparation method is simple in process, the preparation conditions are easy to control, and it is suitable for industrial production. The first problem solved by the present invention is to develop a highly active composite metal oxide catalyst with independent intellectual property rights; the second problem solved by the present invention is to broaden the operating temperature window of the catalyst, especially its low-temperature activity; the third problem solved by the present invention is to adopt a coprecipitation method, the preparation process and method are simple, easy to realize industrial production and low cost.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is:

[0008] A method for preparing a MnSm hydrotalcite-derived catalyst for low-temperature C3H6-SCR degradation comprises the following steps:

[0009] (1) Weigh the active component Mn(NO3)2·4H2O and the auxiliary agent Sm(NO3)3·4H2O in a stoichiometric ratio, add 40 ml of deionized water, and stir until they are completely dissolved to obtain a transparent metal salt solution;

[0010] (2) adding an alkaline stabilizer to 20 ml of deionized water to prepare a stabilizer solution, weighing Na2CO3 with the same molar number as the metal ion and dissolving it in 50 ml of deionized water to prepare a precipitant;

[0011] (3) Add a magnetic stirrer to the precipitant obtained in step (2), rotate and stir in a constant temperature heated magnetic stirrer, and slowly drop the mixed metal salt solution and stabilizer into the beaker containing the precipitant in step (2) to control the pH to be stable. After the dropwise addition is completed, the suspension is aged for 12 hours under vigorous stirring at a constant temperature;

[0012] (4) After several centrifugal washes, the pH value of the supernatant was neutralized, and the resulting precipitate was further dissolved in 100 mL of anhydrous ethanol and stirred for 2 h;

[0013] (5) placing the sample of the precursor obtained in step (4) in an oven and drying overnight;

[0014] (6) Grind the precursor sample obtained in step (5) into fine powder, place it in a muffle furnace, roast it, and cool it naturally to room temperature to obtain a C3H6-SCR NO degradation catalyst.

[0015] According to the above scheme, the precipitant is Na2CO3, and the stabilizer is NaOH, KOH, and NH3·H2O.

[0016] Preferably, the precipitant n(Na2CO3):n(M 2+ +M 3+ )=1:1.

[0017] According to the above scheme, the molar concentration of the stabilizer solution is 0.04M.

[0018] According to the above scheme, n(Mn 2+ ):n(Sm 3+ )=1:n(n=0.25, 0.5, 0.75, 1).

[0019] According to the above scheme, the metal salt solution is added at a rate of 1 ml / min, and the precipitant NaOH is slowly added during the process to maintain the precursor solution pH ≈ 9.5-11.5 ± 0.2.

[0020] According to the above scheme, the precursor solution is aged at room temperature for 9-13 hours, washed with water to neutrality, dried, and finally calcined in an atmosphere such as Air, N2, O2, H2 / Ar, etc. to obtain the MnSm hydrotalcite-derived denitrification catalyst.

[0021] According to the above scheme, the constant temperature aging stirring temperature is 70°C;

[0022] Preferably, the drying temperature is 110°C;

[0023] The drying time is 11-13h;

[0024] The calcination temperature is 400°C;

[0025] The calcination time is 5 hours.

[0026] The present invention also provides the use of a C3H6-SCR NO degradation catalyst prepared by the preparation method described in any one of the above technical solutions in tail gas denitrification.

[0027] The present invention has the following advantages:

[0028] 1. Use C3H6 produced by internal combustion engines as a reducing agent instead of traditional NH3 as a reducing agent, and remove NO produced by internal combustion engines at the same time x and C3H6 are two major pollutants;

[0029] 2. The composite metal oxide catalyst derived from MnSm hydrotalcite has excellent low-temperature catalytic activity and a wide temperature operating window. x The conversion rate is over 50%.

[0030] 3. The MnSm hydrotalcite-derived composite metal oxide catalyst is prepared by co-precipitation method. The preparation method has simple process, low cost, high catalytic activity for SCR reaction, and can purify C3H6 in motor vehicle exhaust gas. The preparation conditions are simple, easy to control, and suitable for industrial production.

[0031] Figure 1 These are catalytic activity test graphs of the catalysts prepared in Examples 1, 2, 3, 4, 5 and 6.

[0032] Figure 2 These are catalytic activity test graphs of the catalysts prepared in Examples 1, 5, 7, 8, 9 and 10.

[0033] Figure 3 These are the catalytic activity test graphs of the catalysts prepared in Examples 1, 11, 12, 13, 14 and 15.

[0034] Figure 4 These are the catalytic activity test graphs of the catalysts prepared in Examples 1, 5, 16, 17 and 18.

[0035] Figure 5 These are the catalytic activity test graphs of the catalysts prepared in Examples 1, 5, 19, and 20.

[0036] Figure 6XRD spectra of the catalysts prepared in Example 1 and Example 19.

[0037] Figure 7 H2-TPR spectra of the catalysts prepared in Example 1 and Example 19.

[0038] Figure 8 XPS spectra of the catalysts prepared in Example 1 and Example 19. DETAILED DESCRIPTION

[0039] The present invention will be further described below through some implementation examples, but the present invention is not limited thereto.

[0040] Example 1

[0041] Weigh 2.3243g of Mn(NO3)2·4H2O in a certain proportion, add 40ml of deionized water to dissolve it to obtain a mixed metal salt solution; weigh 3.2g of NaOH and dissolve it in 20ml of deionized water to obtain a stabilizer, weigh 1.325g of sodium carbonate and dissolve it in 50ml of water to obtain a precipitant; add the mixed metal salt solution dropwise to the precipitant sodium carbonate stirred at a constant temperature of 70°C, and add the precipitant NaOH dropwise during the process to maintain the solution pH≈10. After the addition is completed, continue stirring for 12h to obtain a Mn-LDHs hydrotalcite precursor solution. Then filter and wash until pH≈7, stir the slurry in an ethanol solution for 2h, and finally dry and grind it at 80°C and place it in a muffle furnace for calcination at 400°C for 5h. Press the calcined powder into tablets at a pressure of 10Mpa using a tablet press and crush it to 20-40 meshes to obtain a Mn-LDO catalyst.

[0042] Catalyst Evaluation

[0043] The activity evaluation of the catalyst was carried out in a homemade continuous flow fixed bed reactor. The reaction tube is a quartz tube with an inner diameter of 6mm and a length of 33cm. The reaction temperature is measured by a thermocouple placed in the middle of the reaction tube, and the reaction temperature is controlled by a program temperature controller. The gas flow is controlled by a mass flow meter. The reaction raw gas: 400ppm C3H6, 400ppm NO, 6% O2 and balance gas Ar. In the experiment, the catalyst dosage is 0.2g, the reaction temperature is 150℃~450℃, and sampling is performed every 50℃. The detection is carried out with a flue gas analyzer (MRU, VARIO PLUS) to calculate the conversion rate of NO. The NO conversion curve of the catalyst at different temperature points is shown in the figure below. Figure 1 shown.

[0044] Embodiments 2 to 6

[0045] Compared with Example 1, only n(Mn 2+ ): n(Sm 3+)=1:0.25-1, and the other processes are the same as those in Example 1 to obtain the finished composite metal oxide catalysts. The catalyst compositions of Examples 2 to 6 are shown in Table 1.

[0046] Catalyst Evaluation

[0047] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 1 Its conversion rate and operating window temperature at 150°C are shown in Table 1.

[0048] Embodiments 7 to 10

[0049] The difference from Example 1 is that the aging time of the synthetic precursor MnSm-LDHs hydrotalcite is 9-13 hours. The catalyst compositions of Examples 7 to 10 are shown in Table 1.

[0050] Catalyst Evaluation

[0051] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 2 Its conversion rate and operating window temperature at 150°C are shown in Table 1.

[0052] Examples 11 to 15

[0053] The difference from Example 1 is that the pH of the synthetic precursor MnSm-LDHs hydrotalcite is about 9.5-11.5. The catalyst compositions of Examples 11 to 15 are shown in Table 1.

[0054] Catalyst Evaluation

[0055] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 2 Its conversion rate and operating window temperature at 150°C are shown in Table 1.

[0056] Embodiments 16 to 18

[0057] The difference from Example 1 is that the calcination atmosphere during activation of the MnSm hydrotalcite precursor is Air, N2, O2, or H2 / Ar. The catalyst compositions of Examples 16 to 18 are shown in Table 1.

[0058] Catalyst Evaluation

[0059] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 2 Its conversion rate and operating window temperature at 150°C are shown in Table 1.

[0060] Embodiments 19 to 20

[0061] The difference from Example 1 is that the precipitants used in the synthesis of the MnSm hydrotalcite precursor are: NaOH, KOH, NH3·H2O. The catalyst compositions of Examples 19 to 20 are shown in Table 1

[0062] According to the evaluation method of Example 1, the conversion curve of the catalyst to NO at different temperature points is as follows: Figure 2 Its conversion rate and operating window temperature at 150°C are shown in Table 1.

[0063] Example Metal oxide catalyst composition and surface activity evaluation results: The composition and activity evaluation results of the hydrotalcite-derived composite metal oxide catalyst are shown in Table 1:

[0064] The data in Table 1 show that the denitrification efficiency of catalysts prepared by different ratios of active components to additives, different pH values ​​of coprecipitation, different aging times, different precipitants, and different atmospheres during precursor calcination activation are different. Among them, Mn1Sm was prepared by coprecipitation method, precipitant KOH, aging time 12h, pH stable at about 10, activation calcination in air, and active component Mn and additive Sm metal ion ratio of 1:0.75. 0.75 -LDO-Air-KOH (t=12, pH=10) has the best NOx removal effect in a wide temperature range (150-350°C).

[0065] XRD characterization

[0066] Figure 6 (a) Through the Mn1Sm 0.75 -LDHs, Mn-LDHs precursor structure, Mn1Sm 0.75 -LDHs precursor showed four reflection peaks at 11.82°, 23.26°, 35.96°, and 47.46°, which were respectively attributed to the (003), (006), (012), and (018) crystal planes of the hydrotalcite structure (PDF#37-0630), indicating that the LDHs precursor structure was successfully synthesized, and there were no other diffraction peaks, indicating that the prepared hydrotalcite had a high purity. Figure 6 (b) The precursor LDH was converted into Mn-LDO, Mn1Sm after calcination at 400 °C for 5 hours. 0.75-LDO catalyst XRD spectrum, observed that the characteristic diffraction peaks attributed to LDH disappeared, indicating that the layered structure collapsed, while the Mn-LDO catalyst showed characteristic peaks attributed to Mn3O4 (PDF#19-0803). Due to the introduction of the auxiliary agent Sm, no relevant metal diffraction peaks were observed, indicating that metal Mn and Sm exist in an amorphous state. According to literature reports, this amorphous state has a higher surface energy due to the presence of defects and unstable states, which is conducive to the adsorption and reaction of gases, thereby promoting the catalytic reaction. Combined with the denitration performance test results, the addition of an appropriate amount of Sm can make MnO x It exists in an amorphous state and significantly improves the denitrification activity of the catalyst.

[0067] H2-TPR characterization

[0068] H2-TPR is used to explore the reduction and oxidation capabilities of catalysts. Figure 7 Medium Mn1Sm 0.75 -LDO and Mn-LDO catalysts have three reduction peaks in the range of 240-450℃ attributed to the reduction of metal Mn oxide, of which the peak at 240-290℃ is attributed to the reduction of MnO2→Mn2O3, and the peak at 360-400℃ is attributed to the reduction of Mn2O3→Mn3O4. The peak at 415-500℃ is attributed to the reduction of Mn3O4→MnO; at 725℃, the peak at 415-500℃ is attributed to the reduction of Mn3O4→MnO. 0.75 -LDO catalysts have seen new 3+ →Sm 2+ process; compared with Mn-LDO catalyst, Sm doping further widens the area of ​​the reduction peak. Compared with the reduction peak position, it is found that with the addition of Sm, the reduction peak position moves toward the low temperature direction, which may be the result of strong electron transfer between Mn and Sm. From the results, it can be seen that the order of reduction ability should be Mn1Sm 0.75 -LDO>Mn-LDO, indicating that after Sm doping, Mn1Sm 0.75 -The redox ability of the LDO catalyst is improved. The improvement of reducibility is beneficial to the Mn1Sm 0.75 -The oxygen on the LDO surface dehydrogenates C3H6, thereby improving the C3H6-SCR activity.

[0069] XPS characterization

[0070] In order to study the effects of the valence state and composition of the catalyst surface elements on the catalyst performance, XPS analysis was performed on a series of catalysts. Figure 8 The XPS results of different samples of Mn 2p, Sm 3d, and O 1s are given. Figure 8In (a), the O1s spectra of the two catalysts are well deconvoluted into two peaks: the peak at the lower binding energy of 528.68-529.61 eV can be attributed to the lattice oxygen O β , surface adsorbed oxygen O at 531.78-530.66 eV α In particular, when redox reactions occur, O a The mobility is greater than O β The mobility of O a O β More active, so the O a The more it is, the more conducive it is to the redox reaction. Figure 8 (c) Mn1Sm 0.75 The XPS spectrum of the -LDO catalyst in Sm 3d can be decomposed into two peaks with binding energies of 1083.7eV and 1081.6eV, representing Sm 3+ and Sm 2+ Mn1Sm 0.75 Mn 2p spectra of Mn-LDO and Mn-LDO catalysts are shown in Figure 2 Figure 8 (b) shows that the peak with a binding energy of 641.7 eV refers to the Mn 2p 3 / 2 , the peak with a binding energy of 653.8 eV is Mn 2p 1 / 2 Among them, the peaks at 640.4eV, 642.2eV and 643.3eV are attributed to Mn 2+ , Mn 3+ and Mn 4+ This indicates that the manganese oxide species in the two catalysts are mainly in the form of high-valent Mn 4+ and Mn 3+ Exist in the form of Mn 3+ and Mn 4+ It is generally considered to be the main active component of low-temperature SCR reaction. 4+ Species and Mn 4+ / Mn 3+ The species plays an important role in promoting the low-temperature C3H6-SCR reaction of the catalyst, which is beneficial to improving the low-temperature catalytic activity of the catalyst.

Claims

1. A preparation method and application of a MnSm hydrotalcite-derived catalyst for low-temperature SCR degradation, characterized in that: The method comprises the following steps: (1) Weigh the active component Mn(NO3)2·4H2O and the auxiliary agent Sm(NO3)3·4H2O in the stoichiometric ratio, add 40 ml of deionized water, and stir until they are completely dissolved to obtain a transparent solution; (2) adding an alkaline stabilizer to 20 ml of deionized water to prepare a stabilizer solution, weighing Na2CO3 with the same molar number as the metal ion and dissolving it in 50 ml of deionized water to prepare a precipitant; (3) Add a magnetic stirrer to the precipitant obtained in step (2), rotate and stir in a constant temperature heated magnetic stirrer, and slowly drop the mixed metal salt solution and stabilizer into the beaker containing the precipitant in step (2) to control the pH to be stable. After the dropwise addition is completed, the suspension is aged for 12 hours under vigorous stirring at a constant temperature; (4) After several centrifugal washes, the pH value of the supernatant was neutralized, and the resulting precipitate was further dissolved in 100 mL of anhydrous ethanol and stirred for 2 h; (5) placing the sample of the precursor obtained in step (4) in an oven and drying overnight; (6) Grind the sample obtained in step (5) into fine powder, place it in a muffle furnace, roast it, and cool it naturally to room temperature to obtain a C3H6-SCR NO degradation catalyst.

2. The method for preparing a MnSm hydrotalcite-derived catalyst for low-temperature SCR NO degradation catalyst according to claim 1, characterized in that: The preparation method is a co-precipitation method, and the ratio of the precipitant to the total metal ions is (Na2CO3: Mn 2+ +Sm 3+ =1:1).

3. The method for preparing a MnSm hydrotalcite-derived catalyst for C3H6-SCR NO degradation catalyst according to claims 1-2, characterized in that: The molar ratio of the metal elements in the metal salt solution is: 2+ ):n(Sm 3+ )=1:n(n=0.25, 0.5, 0.75, 1).

4. The method for preparing the MnSm hydrotalcite-derived catalyst for C3H6-SCR NO degradation catalyst according to any one of claims 1 to 4, characterized in that: The metal salt solution was added at a rate of 1 ml / min, and the precipitant NaOH was slowly added during the process to maintain the precursor solution pH ≈ 9.5-11.5 ± 0.

2.

5. The method for preparing the MnSm hydrotalcite-derived catalyst for C3H6-SCR NO degradation catalyst according to any one of claims 1 to 5, characterized in that: The precursor solution is aged at room temperature for 9-13 hours, washed with water until neutral, dried, and finally calcined in an atmosphere such as Air, N2, O2, H2 / Ar, etc. to obtain the MnSm hydrotalcite-derived denitrification catalyst.

6. The method for preparing the MnSm hydrotalcite-derived catalyst for C3H6-SCR NO degradation catalyst according to any one of claims 1 to 6, characterized in that: The stabilizers are NaOH, KOH, and NH3·H2O.

7. The method for preparing the MnSm hydrotalcite-derived catalyst for C3H6-SCR NO degradation catalyst according to any one of claims 1 to 6, characterized in that: The constant temperature aging stirring temperature is 70°C; The calcination temperature is 400°C; The calcination time is 5 hours.

8. A method for preparing a MnSm hydrotalcite-derived catalyst for low-temperature SCR NO degradation catalyst according to any one of claims 1 to 7.

Citation Information

Cited By

  • Hydrotalcite-like derivative metal oxide catalyst and preparation method and application thereof

    CN122252186A